Evaluasi Kebijakan Penurunan Tarif Parkir di Kota Magelang: Studi Kualitatif Penerapan Tarif dan Kepatuhan Jukir - Riflah Nabilah; Oktavia Choirunnisa; Mifta Khoirul Putri Rahayu; Miza Putri Rizanti (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
The Magelang City Government’s policy to reduce parking rates, which is regulated in Regional Regulation Number 11 of 2025, responds to public complaints regarding the increase in rates reaching 100% in 2023 which is considered to be very burdensome for economic activities. This descriptive qualitative research evaluates the effectiveness of policies using William N. Dunn’s six criteria (effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy), with respondents from the Transportation Service, parking attendants, and service users in eight strategic locations through in-depth interviews, observations, and documents. As a result, the policy succeeded in reducing the public’s cost burden. However, obstacles still occur, such as tariff inconsistencies, compliance violations by parking attendants, and a decrease in parking attendants’ daily income from IDR 90,000 to IDR 60,000. The application of tariffs is also not evenly distributed at all points. Despite the positive public response, complaints regarding the consistency of the rules and the attitude of officers still exist. Research recommendations include strengthening technology-based supervision, improving the welfare of parking attendants through incentives, wider outreach, accelerating electronic parking, as well as structuring locations and controlling illegal parking attendants to bridge the gap between regulatory objectives and field realities.